EFEKTIFITAS KOMBINASI PUPUK ANORGANIK DAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JUNGGULAN (Crassocephalum crepidioides) - hermawan susanto; Mahayu Woro Lestari; Novi Arfarita (AGRONISMA, 2020)
This study aims to determine the effectiveness of a combination of inorganic fertilizers and the interval of biological fertilizer on the growth of superior crops (crassocephalum crepidiodes). This research was conducted in Pendem Village, Junrejo District, Batu City and integrated laboratory of Islamic University of Malang with the height of the area Â± 641 meters above sea level, average temperature of 20Âº C. Rainfall 30 mm. This research was conducted in December 2018 until March 2019. This research uses factorial randomized block design (RBD) consisting of 2 factors. Factor 1 is the composition of inorganic fertilizer (P) consisting of 4 levels, namely P0 (without the provision of inorganic fertilizer), P1 (100 kg urea Ha-1), P2 (100 kg urea Ha-1 + 25 kg TSP Ha-1), P3 (100kg urea Ha-1 + 25 kg TSP Ha-1 + 25 kg KCl Ha-1). Factor 2 is the interval of biological fertilizer (K) consisting of 4 levels, namely, K0 (without the administration of Ultra-gen fertilizer), K1 (Provision of Ultra-gene fertilizer once every 5 days), K2 (Provision of Ultra-gene fertilizer once every 7 days) and K3 (Provision of Ultra gene fertilizer every 9 days) from 2 factors obtained 16 combinations, each treatment contained 3 samples and repeated 3 times so that there were 144 samples.The results of this study indicate that there is an interaction between inorganic fertilizers and biological fertilizer intervals. In general, inorganic fertilizer treatment yields tend to yield better results on the growth and yield of predominantly dominated plants in the P3 treatment (100kg urea Ha-1 + 25 kg TSP Ha-1 + 25 kg KCl Ha-1). Biological fertilizer treatment can provide interaction with plant height, leaf area.